MAKNA KEARIFAN BUDAYA JAWA DALAM PUISI PARIKSIT, TELINGA, DONGENG SEBELUM TIDUR, DAN ASMARADANA - Heri Suwignyo (Fakultas Sastra Universitas Negeri Malang, 2013)
The interpretation of Javanes wisdom can be found in Indonesian modern poetry by decoding the cultural tradition of wayang story, mystical stories and folklore. One of Javanes wisdom ojo dumeh (don’t be arrogant) is found in the poem Parksit and revealed in chapter VII. “Telinga” poetry exposed the value of cultural wisdom Java manunggaling kawula Gusti (self discovery), from the mystical story of Dewa Ruci. The poem “Asmaradana” and “Dongeng Sebelum Tidur” showed the meaning of sincerity sacrifice and firmness in keeping promises which was inpired by a folklore entitled King Anglingdarma and Damarwulan.